Cinnamaldehyde, a Promising Natural Preservative Against Aspergillus flavus - Qu, Su; Yang, Kunlong; Chen, Lei; Liu, Man; Geng, Qingru; He, Xiaona; Li, Yongxin; Liu, Yongguo; Tian, Jun (Frontiers in Microbiology, 2019)
The problem of food spoilage due to Aspergillus flavus (A. flavus) needs to be resolved. In this study, we found that the minimum inhibitory concentration (MIC) of cinnamaldehyde (CA) that inhibited A. flavus was 0.065 mg/ml and that corn can be prevented from spoiling at a concentration of 0.13 mg/cm3. In addition to inhibiting spore germination, mycelial growth, and biomass production, CA can also reduce ergosterol synthesis and can cause cytomembrane damage. Our intention was to elucidate the antifungal mechanism of CA. Flow cytometry, fluorescence microscopy, and western blot were used to reveal that different concentrations of CA can cause a series of apoptotic events in A. flavus, including elevated Ca2+ and reactive oxygen species (ROS), a decrease in mitochondrial membrane potential (Δψm), the release of cytochrome c, the activation of metacaspase, phosphatidylserine (PS) externalization, and DNA damage. Moreover, CA significantly increased the expression levels of apoptosis-related genes (Mst3, Stm1, AMID, Yca1, DAP3, and HtrA2). In summary, our results indicate that CA is a promising antifungal agent for use in food preservation.